Pengaruh Metode Pembelajaran Index Card Match Terhadap Hasil Belajar Siswa Pada Mata Pelajaran PAI - Fauziah, Hapsah; Halimatussaadah, Nurul (MASAGI : Jurnal Pendidikan Agama Islam, 2024)
Learning outcomes are the abilities acquired by students after undergoing the learning process, involving relatively permanent behavioral changes. This learning process encompasses goals set by teachers, including cognitive, affective, and psychomotor abilities. According to research findings, many students' learning outcomes in the subject of Islamic Religious Education (PAI) are below the Minimum Competency Criteria (KKM). One contributing factor is the frequent use of monotonous strategies, methods, and media by teachers during the teaching process, causing students to feel bored and unmotivated to achieve good results. The Index Card Match method is a teaching approach that encourages students to collaborate and enhances their responsibility for what they learn in an enjoyable manner. This collaborative learning activity helps foster active learning and teaching abilities through small group cooperation, allowing students to achieve better understanding and mastery of the material. The objectives of this study are: To describe the learning outcomes in PAI before the implementation of the Index Card Match method. To describe the learning outcomes in PAI after the implementation of the Index Card Match method. To describe the impact of the Index Card Match method on the learning outcomes in PAI. This research employs an experimental method with a quasi-experimental design. The study sample consists of 16 students in the experimental group and 16 students in the control group. The findings indicate that the Index Card Match method significantly influences students' learning outcomes in the subject of Islamic Religious Education on the topic of understanding the divine scriptures. This is evidenced by the statistical results showing a significance value (Sig.) of 0.000 < 0.05, indicating that the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This signifies that there is a significant impact of the Index Card Match method on improving students' learning outcomes in the PAI subject.  Keywords: Index Card Match Method, Learning Outcomes, Islamic Religious Education (PAI)